Application of Skarn Deposit Zonation Models to Mineral Exploration - Lawrence D. Meinert (Canadian Institute of Mining, Metallurgy and Petroleum, 1997)
Abstract-Most large skarn deposits are zoned in both space and time relative to associated intrusions. Zonation occurs on scales from kilometers to micrometers, and reflects infiltrative fluid flow, wallrock reaction, temperature variations, and fluid mixing. The most spectacular examples of skarn zonation usually occur at the skarn-marble contact, where transitions between monomineralic bands can be knife sharp. Other small-scale examples occur in zoned veins and individual mineral crystals. Although, visually striking and scientifically interesting, in mineral exploration these small-scale variations are less useful than deposit- or district-scale zonation. In most skarn systems there is a general zonation pattern of proximal garnet, distal pyroxene, and vesuvianite (or a pyroxenoid such as wollastonite, bustamite, or rhodonite) at the marble front. As well, individual skarn minerals may display systematic color or compositional variations within the larger zonation pattern. Such patterns are reviewed for 14 well-studied examples of Cu, W, Sn, Au, and Zn-Pb skarns. In addition, many deposits have endoskarn or other alteration of the associated intrusion, and recrystallization or other subtle changes have occurred in the surrounding wallrocks. Copper skarns, such as Mines Gaspé in Quebec and Big Gossan in Irian Jaya, have high ratios of garnet:pyroxene and are zoned outward from the intrusion, to garnet, to pyroxene, to massive-sulfide replacement and vein deposits. Garnets in Cu skarn are Fe-rich and change from dark red-brown near the intrusive contact to paler brown, green, or yellow in distal locations. Pyroxenes in Cu skarns are pale and diopsidic near the intrusion, and become darker and more Fe- and Mn-rich away from the intrusion. Tungsten skarns, such as Salau and Costabonne in France and Pine Creek and Garnet Dike in California, have intermediate ratios of garnet:pyroxene, are more extensive vertically and along strike than perpendicular to the intrusive contact, and have zonation patterns commonly complicated by overprinting of metamorphic lithologies. In W skarns, garnet is commonly subcalcic and the pyroxene is Fe-rich, reflecting particularly reducing wallrocks or great depth of formation. Tin skarns, such as Dachang in China and Moina in Australia, also can have subcalcic garnet and Fe-rich pyroxene, but this reduced mineral assemblage typically is due to an association with reduced S-type granites. Tin skarns differ from most other skarn types in having a late greisen stage that may replace earlier Sn-bearing calc-silicate minerals, thus liberating Sn to form cassiterite. Many high-grade Au skarns, such as Hedley in British Columbia and Fortitude in Nevada, have low ratios of garnet:pyroxene and are associated both with reduced plutons and reduced wallrocks. Goldrich zones occur in Fe-rich, pyroxene-dominant, distal skarn. Zn-Pb skarns, such as the Yeonhwa- Ulchin district in Korea and Groundhog in New Mexico, have low ratios of garnet:pyroxene and generally form distal to associated intrusions. These skarns also are zoned from proximal garnet to distal pyroxene and pyroxenoid (bustamite-rhodonite), with significant zones of massive sulfides within and beyond skarn. Manganese enrichment of most mineral phases, particularly pyroxene, is characteristic of distal zones. Fundamental controls on skarn zonation include temperature, depth of formation, composition and oxidation state of associated plutons and wallrocks, and tectonic setting. Most W skarns form at relatively great depth, 5 km to 20 km, with extensive high-temperature metamorphic and metasomatic mineral assemblages. In contrast, most other skarn types are relatively shallow, <10 km and mostly <5 km, with limited, lower temperature metamorphic aureoles. Differences in oxidation state correlate well with different skarn zonation patterns, particularly garnet:pyroxene ratios and compositions, and can be used in both classification of and exploration for s